Alkaline phosphatase and bilirubin combined are a powerful predictor of outcome in patients with heart failure and reduced ejection fraction: an analysis of the ATMOSPHERE and PARADIGM-HF trials. (3rd October 2022) - Adamson, C; Butt, J H; Rouleau, J; Abraham, W; Desai, A; Dickstein, K; Kober, L; Lefkowitz, M P; Packer, M; Petrie, M C; Swedberg, K; Solomon, S D; et al.
Abstract: Introduction: Bilirubin is a recognized predictor of adverse outcomes in patients with heart failure and reduced ejection fraction (HFrEF), possibly because it is a marker of congestion. Alkaline phosphatase (ALP) is an enzyme produced in many tissues including the biliary ducts and elevated levels are also associated with congestion. Purpose: To examine the prognostic value of ALP alone and in combination with bilirubin in patients with HFrEF. Methods: The study population was ambulatory patients with HFrEF enrolled in 2 recent clinical trials with similar inclusion and exclusion criteria: ATMOSPHERE (derivation cohort) and PARADIGM-HF (validation). Cut points to define elevated bilirubin and alkaline phosphatase were >17mg/dL and >120 U/L respectively. The composite of cardiovascular death or HF hospitalization, its components, and all-cause death related to elevation of one, other or both of bilirubin and ALP was examined using Cox regression. Univariable and multivariable models with adjustment for other recognized prognostic variables including NT-proBNP were analyzed. Results: Of 7016 patients with HFrEF enrolled in ATMOSPHERE, 6870 had a measurement of both bilirubin and ALP at baseline: mean age 63 years, 22% women, mean LVEF 28% and proportion NYHA class III/IV 37%. Bilirubin and ALP were both normal in 4810 (70.0%) patients, bilirubin was elevated in 1393 (20.3%), ALP was elevated in 360 (5.2%) and both were elevated in 307 (4.5%) patients. Patients with elevation of both ALP and bilirubin were older, had lower systolic blood pressure, higher heart rate, higher NT-pro BNP, more clinical features of congestion, more atrial fibrillation and a greater proportion were treated with diuretics and digoxin. The primary endpoint rates (per 100 person-years) were 10.4 (95% CI 9.9–11.0) when both markers were normal, 15.1 (13.9–16.4) when bilirubin was elevated, 12.4 (10.4–14.9) when alkaline phosphatase was elevated, and 25.6 (22.0–29.9) when both markers were elevated (Figure 1). The adjusted hazard ratios (95% CI) were (both biomarkers normal = reference): elevated bilirubin 1.19 (1.07–1.31), P=0.001; elevated ALP 1.03 (0.84–1.26), P=0.81; both elevated 1.45 (1.21–1.73), P<0.001. Elevation of both bilirubin and ALP was a significant independent predictor of the components of the primary outcome and all-cause death, the corresponding hazard ratios for all cause death were 1.12 (0.99–1.25), p=0.06; 1.19 (0.96–1.47), p=0.12; and 1.51 (1.25–1.82), p<0.001. These findings were validated in PARADIGM-HF (Table 1). Conclusions: Elevation of ALP in combination with elevated bilirubin identifies a small group of patients at very high risk of adverse outcomes. This may reflect more significant congestion. ALP and bilirubin, inexpensive and routinely measured biochemical tests, are useful prognostic markers in patients with HFrEF. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship.